Child maltreatment data: A summary of progress, prospects and challenges. (September 2021) - Fluke, John D.; Tonmyr, Lil; Gray, Jenny; Bettencourt Rodrigues, Leonor; Bolter, Flora; Cash, Scottye; Jud, Andreas; Meinck, Franziska; Casas Muñoz, Abigail; O'Donnell, Melissa; Pilkington, Rhiannon; Weaver, Leemoy
Abstract: Background: In 1996, the ISPCAN Working Group on Child Maltreatment Data (ISPCAN-WGCMD) was established to provide an international forum in which individuals, who deal with child maltreatment data in their respective professional roles, can share concerns and solutions. Objective: This commentary describes some of the key features and the status of child maltreatment related data collection addressed by the ISPCAN-WGCMD. Methods: Different types of data collection methods including self-report, sentinel, and administrative data designs are described as well as how they address different needs for information to help understand child maltreatment and systems of prevention and intervention. Results: While still lacking in many parts of the world, access to child maltreatment data has become much more widespread, and in many places a very sophisticated undertaking. Conclusion: The ISPCAN-WGCMD has been an important forum for supporting the continued development and improvement in the global effort to understand and combat child maltreatment thus contributing to the long term goals of the UN Convention on the Rights of the Child. Nevertheless, based on what has been learned, even greater efforts are required to improve data in order to effectively combat child maltreatment.